The Effect of Intermittent Hemodialysis on the Hematological and Serum Biochemistry Profile in Dogs With Chronic Kidney Disease - Geraldes, Silvano Salgueiro [UNESP]; Le Sueur, André Nanny Vieira [UNESP]; Sant'Ana, Paula Bilbau [UNESP]; de Azevedo, Maria Gabriela Picelli [UNESP]; Takahira, Regina Kiomi [UNESP]; Melchert, Alessandra [UNESP]; Lourenço, Maria Lucia G. [UNESP]; Mamprim, Maria Jaqueline [UNESP]; Guimarães-Okamoto, Priscylla Tatiana Chalfun [UNESP] (Elsevier, 2020)
Intermittent hemodialysis (IHD) is a type of kidney replacement therapy commonly prescribed in veterinary medicine for cases of drug removal, fluid, acid-base, and electrolyte disorders, acute kidney injury, and cases of chronic kidney disease (CKD) in uremic crisis. This study aimed to evaluate the effects of intermittent hemodialysis in dogs with IRIS stage 4 CKD in contrast to dogs treated only with standard medical management, without dialysis, to improve their quality of life. Twenty-five dogs previously diagnosed with IRIS stage 4 CKD were selected for the study according to the inclusion criteria. Dogs were randomized to 2 distinct groups: the control group (n = 11), which underwent a conventional clinical treatment for CKD; and the hemodialysis group (n = 14), which underwent intermittent hemodialysis in addition to the clinical treatment. Both groups had a period of 15 days of clinical and laboratory evaluation. Laboratory analysis consisted of chemistry and hematological evaluation before and after both treatments at a minimum interval of 48 hours. Clinical parameters and eventual complications were assessed every 30 minutes during the IHD. When compared with conventional treatment, IHD was highly efficient in removing urea, creatinine, and phosphorus, but presented a hematological risk to the patient, requiring constant monitoring of hematological and biochemical profiles in order to correct alterations. Therefore, IHD is a highly recommended treatment if adequately monitored by trained professionals.
Keywords: dialysis; diffusion; Dogs; kidney diseases